The Chinese version of the tendency to stigmatize epidemic diseases scale: a translation and validation study - Wang, Xin; Wang, Yuecong; Ge, Yuanhui; Liu, Yuxiu; Niu, Riyu; Guo, Zhengxiang; Ge, Dongfang (Frontiers in Psychiatry, 2024)
Objective: To translate the Tendency to Stigmatize Epidemics Diseases Scale (TSEDS) into Chinese and to evaluate its psychometric properties. Methods: Translation and cross-cultural adaptation using the Brislin translation model, and pre-testing to form a Chinese version of TSEDS. A total of 434 adults participated in the study and the TSEDS were measured using the critical ratio method, Pearson correlation analysis, retest reliability, content validity, structural validity, and concurrent validity.The Chinese version of the TSEDS scale contains 27 items in 5 dimensions, including structural stigma, perceived stigma, organizational stigma, internalized stigma, and social stigma. The average content validity index of the scale was 0.975. The goodness of fit index ( χ2/df= 1.981, RMSEA = 0.067, CFI= 0.930, IFI = 0.931, TLI = 0.922) indicated a good model fit. The Cronbach's alpha coefficient was 0.962 and the dimensionality ranged from 0.882 to 0.928. The retest reliability was 0.912.The Chinese version of TSEDS has good reliability and validity, which can be used to assess the epidemiological stigma tendency of Chinese adults.